2019
DOI: 10.1021/acs.jpca.9b05350
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of S2 (X3Σg, a1Δg, and b1Σg+) in the 320–205 nm Region

Abstract: Photodissociation of vibrationally and electronically excited sulfur dimer molecules (S 2 ) has been studied in a combined experimental and computational quantum chemistry study in order to characterize bound-continuum transitions. Ab initio quantum chemistry calculations are carried out to predict the potential energy curves, spin–orbit coupling, transition moments, and bound-continuum spectra of S 2 for comparison with the experimental data. The experiment uses v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…All signals corresponded to one-photon dissociation to DL 0 ; no signals for two-photon dissociation (to 3 P products) or to photodissociation of S 2 + ions were observed. In our other study of the metastable state S 2 (a 1 Δ g , b 1 Σ g + ), around 310 nm 25 onephoton dissociation is also the stronger channel compared to two-photon dissociation processes. At the S( 1 S) and S( 1 D) REMPI wavelengths longer than 280 nm, two-photon dissociation was found to be stronger than three-photon dissociation to S* or dissociation of S 2 + .…”
Section: Relative Strengths Of the Multiphotonmentioning
confidence: 75%
See 4 more Smart Citations
“…All signals corresponded to one-photon dissociation to DL 0 ; no signals for two-photon dissociation (to 3 P products) or to photodissociation of S 2 + ions were observed. In our other study of the metastable state S 2 (a 1 Δ g , b 1 Σ g + ), around 310 nm 25 onephoton dissociation is also the stronger channel compared to two-photon dissociation processes. At the S( 1 S) and S( 1 D) REMPI wavelengths longer than 280 nm, two-photon dissociation was found to be stronger than three-photon dissociation to S* or dissociation of S 2 + .…”
Section: Relative Strengths Of the Multiphotonmentioning
confidence: 75%
“…In the UV wavelength region, images were recorded under tight focusing conditions. In our previous two-color study, we reported images taken with the dissociation laser in the 281–266 nm region at low laser intensity and the detection laser tightly focused for S( 3 P J ) detection around 308 nm . With tight focusing in the region below 288 nm, strong S + images were found at or near the wavelengths corresponding to the X ( 3 Σ g – ) – B ( 3 Σ u – )( v ′) bands shown schematically in the energy level diagram of Figure and in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations